2023
DOI: 10.1007/s13534-023-00274-y
|View full text |Cite
|
Sign up to set email alerts
|

Cortical representation of musical pitch in event-related potentials

Abstract: Neural coding of auditory stimulus frequency is well-documented; however, the cortical signals and perceptual correlates of pitch have not yet been comprehensively investigated. This study examined the temporal patterns of event-related potentials (ERP) in response to single tones of pitch chroma, with an assumption that these patterns would be more prominent in musically-trained individuals than in non-musically-trained individuals. Participants with and without musical training (N = 20) were presented with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Even after controlling for musical ability, IQ, and short-term memory (STM), musicians are better at detecting changes in 1-s auditory scenes comprising four events (e.g., animal or environmental sounds; Vanden Bosch der Nederlanden et al 2020). In an electroencephalography (EEG) study, musicians outperformed nonmusicians in a pitch-discrimination task and showed marginally stronger correlations between pitch changes and the amplitude of brain responses, even though group differences disappeared after correction for multiple comparisons (Kim et al 2023).…”
Section: Listening Abilitiesmentioning
confidence: 99%
“…Even after controlling for musical ability, IQ, and short-term memory (STM), musicians are better at detecting changes in 1-s auditory scenes comprising four events (e.g., animal or environmental sounds; Vanden Bosch der Nederlanden et al 2020). In an electroencephalography (EEG) study, musicians outperformed nonmusicians in a pitch-discrimination task and showed marginally stronger correlations between pitch changes and the amplitude of brain responses, even though group differences disappeared after correction for multiple comparisons (Kim et al 2023).…”
Section: Listening Abilitiesmentioning
confidence: 99%
“…Some researchers approach cognitive data as a regression problem [6,7,26,50] while some of them handled the analysis of such data sets as a classification task [4,25,45]. In their multivariable analyses, Assari et al (2021) [2] fit four linear regression to model left lateral orbitofrontal cortex activity during the n-back task.…”
Section: Introductionmentioning
confidence: 99%